Rhabdomyolysis secondary to COVID-19 infection and vaccination: a review of literature - Karimi, Mehdi; Faal Hamedanchi, Neda; Ansari, Kazem; Nahavandi, Reza; Mazdak, Mahsa; Javaherchian, Fateme; Koochaki, Pooneh; Asadi Anar, Mahsa; Shirforoush Sattari, Mahsa; Mohamaditabar, Mona (Frontiers in Medicine, 2024)
Rhabdomyolysis (RML), characterized by the breakdown of skeletal muscle fibers and the release of muscle contents into the bloodstream, has emerged as a notable complication associated with Coronavirus disease 2019 (COVID-19) infection and vaccination. Studies have reported an increased incidence of RML in individuals with severe COVID-19 infection. However, the exact mechanisms remain unclear and are believed to involve the host's immune response to the virus. Furthermore, RML has been documented as a rare adverse event following COVID-19 vaccination, particularly with mRNA vaccines. Proposed mechanisms include immune responses triggered by the vaccine and T-cell activation against viral spike proteins. This study aims to review the current literature on the incidence, pathophysiology, clinical presentation, and outcomes of RML secondary to COVID-19 infection and vaccination.We identify common risk factors and mechanisms underlying this condition by analyzing case reports, clinical studies, and pharmacovigilance data. Our findings suggest that while RML is a relatively rare adverse event, it warrants attention due to its potential severity and the widespread prevalence of COVID-19 and its vaccines. This review underscores the need for heightened clinical awareness and further research to optimize management strategies and improve patient outcomes in this context.